Konsep Kecantikan dalam Iklan: Pendekatan Semiotika Roland Barthes pada Iklan Citra Pearl White UV Hand and Body Lotion - Martha Nur’aini; Wulan Nurhayati; Yayang Aisyah Nurhidayah; Anas Malik (CV. ITTC INDONESIA, 2024)
This study examines the concept of beauty in the Citra Pearl White UV Hand and Body Lotion advertisement using Roland Barthes' semiotic analysis. The main focus of the research is to understand how this advertisement shapes societal perceptions of beauty, particularly regarding fair skin. The aim of the study is to analyze the visual and verbal elements in the advertisement to reveal the denotative and connotative meanings associated with the representation of beauty. The research method employed is a qualitative approach with semiotic analysis. The results show that the Citra advertisement highlights fair skin as a symbol of ideal beauty, associated with wealth and attractiveness. This advertisement reinforces narrow beauty stereotypes, neglecting the diversity of beauty standards, and creates social pressure to conform to a specific standard of beauty, especially among women.